Towards Sound Accessibility in Virtual Reality - Jain, Dhruv; Junuzovic, Sasa; Ofek, Eyal; Sinclair, Mike; Porter, John; Yoon, Chris; Machanavajhala, Swetha; Morris, Meredith Ringel (ACM International Conference on Multimodal Interaction (ICMI2021), 2021)
Abstract Virtual reality (VR) leverages sight, hearing, and touch senses to convey virtual experiences. For d/Deaf and hard of hearing (DHH) people, however, information conveyed through sound may not be accessible. While prior work has explored making every day sounds accessible to DHH users, the context of VR is, as yet, unexplored. In this paper, we provide a first comprehensive investigation of sound accessibility in VR. Our primary contributions include a design space for developing visual and haptic substitutes of VR sounds to support DHH users and prototypes illustrating several points within the design space. We also characterize sound accessibility in commonly used VR apps and discuss findings from early evaluations of our prototypes with 11 DHH users and 4 VR developers. ACM ICMI 2021 Presentation Sound-to-visual and Sound-to-haptic prototypes Source code Coming soon